The importance of addition, competition, collisions of law principles for enforcement and other types of legal activities - S. V. Biryukov (Правоприменение, 2022)
The subject of this research is the problem of combining (interrelation) of various principles of law used in the framework of law enforcement and other types of legal activity.The purpose of the study is to confirm or refute the hypothesis that the principles of law can not only complement each other, but also "collide" with each other when they are used in the framework of legal activity.The research methodology includes dialectics, systems approach, specific sociological methods, culturological and theoretical-sociological analysis, formal legal method. The author describes the degree of scientific elaboration of the problem in foreign and Russian studies, including works devoted to such related topics as the functions of the principles of law and the system of principles of law, as well as the opinions directly on the issue of R. Dworkin and A. Barak.The main results, scope of application. The author substantiates the presence of at least three ways of combining (interconnecting) the principles of law: (1) addition – the concerted action of several principles; (2) competition – limiting the operation of one principle to another; (3) collision – direct contradiction of one principle to another, their mutual exclusion. The definition of factual circumstances, the choice of applicable rules and their interpretation by court or other enforcement official can be influenced by ideology underlying the prevailing practice or the enforcer's own position. The specificity of a particular ideology is correlated by the author with the use of one or another combination of principles of law when making a law enforcement decision. It is shown in the article with specific examples of so-called "complex cases" from the practice of Russian higher courts. Complementing the principles of law is the predominant way of their relationship, used in law enforcement. It contributes to the preservation of the unity of the system of law. At the same time, the consistent implementation of one principle can limit the possibilities for the implementation of others. It leads to the fact in the process of law enforcement that it is often necessary to make a choice in favor of one of the principles within the framework of their competition. This choice is determined by several factors, including not only the established practice (law enforcement customs and precedents), but also the current social context, the position and interests of the law enforcement officer and the participants in the case. Finally, in some cases, situations are possible when the principles of law are mutually exclusive, come into conflict with each other. This, in particular, can occur when the principles of law belong to different systems (subsystems) of law or reflect the peculiarities of the legal ideology of different historical periods. The article identifies certain patterns of combining the principles of law, examines the importance of this topic for studying the issues of legal monism and legal pluralism, shows the importance of complementarity, competition and conflict of principles of law not only for the law enforcement process, but also for the knowledge of law, criticism of law, lawmaking, powerless implementation rights.Conclusions. Although within the framework of the traditional approach for domestic jurisprudence, the essence of law is associated with the interests and property relations reflected in the law, legal ideology has a relatively independent meaning nevertheless. A certain duality is inherent in legal activity, as a result of which the problems of combining interests are expressed precisely through various options for combining the principles and norms of law. It is proved that the system of principles of law is a complex system in which the same principles can be used in various combinations with each other.